Are there border effects in the EU wage function? - Peter Huber; Michael Pfaffermayr; Yvonne Wolfmayr (Center for Economic Studies and ifo Institute (CESifo), 2006)
We estimate a linear approximation of the market potential function for Europe as derived in geography and trade models. Using a spatial econometric estimation approach, border effects are identified by a differential impact of other regions purchasing power, depending on whether two regions are located within the EU15 or outside the EU15. We find that intra EU15-borders have an insignificant but external borders a significant effect on regional wage structures. We illustrate the magnitude of EU external border effects by simulating the enlargement of the EU in May 2004. Our results suggest a large impact of the border for new member states, but a relatively small one for old members.
Keywords: F10; R12; F12; C21; 330